On extension of near-wall domain decomposition to turbulent compressible flows. (15th October 2020) - Petrov, M.; Utyuzhnikov, S.; Chikitkin, A.; Titarev, V.
Highlights: We apply near-wall domain decomposition (NDD) for compressible turbulent flows for the first time. We propose an Exact NDD and compare it against the Approximate NDD earlier developed. We demonstrate the efficiency of NDD and its applicability to flows past complex configurations. Abstract: For modeling turbulent flow, the near-wall domain decomposition (NDD) approach initially proposed by the second author and recently developed in a number of papers proved to be very efficient. It leads to a non-overlapping domain decomposition with a Robin-to-Dirichlet map between an inner (near-wall) and outer regions. The regions are linked with each other via interface boundary conditions of Robin type which equivalently replace both the boundary conditions at the wall and simplified governing equations in the inner region. As has been shown, this approach can reduce the computational time by one order of magnitude while retaining sufficiently high accuracy. In the current paper, for the first time the technique is extended to compressible gas flows. In addition, it is modified to include an exact domain decomposition applied to the original Reynolds-averaged Navier-Stokes equations (RANS) without any simplifications near the wall. The efficiency and accuracy of the algorithm are demonstrated on a number of test cases with the use of the Spalart-Allmaras turbulence model for compressible flows implemented in the in-house code "FlowModellium". Apart from the approximate NDD (ANDD) based on the thin boundary layer model, for the first time an exact NDD (ENDD) is implemented. The interface boundary conditions in both ANDD and ENDD approaches are consistent. Thereby, the ENDD can effectively complete the ANDD approach when it is needed.